DGM621: Social media marketing / Faculty of Business and Management - UiTM, Faculty of Business and Management (2023)
This course covers the planning and integration of social media into marketing plans. The students will learn to set objectives, develop a social marketing plan, integrated social media into the overall marketing and communication plans, measure program results, utilize new media technologies and about the macro-environmental issues affecting social media.